2022
DOI: 10.3389/fbuil.2021.804216
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Influence of the Building Material on the Indoor Air Quality in Apartment in Dubai

Abstract: The residents of Dubai spend more than 90% of their time indoors and this lifestyle makes them easily exposed to Sick Building Syndrome (SBS). Even though Dubai Municipality strictly apply the IAQ (Indoor Air Quality) stipulation, indiscreet use of unproven finishing materials has been increased to deteriorate the health of residents in Dubai. The objective of this paper is to investigate the degree of influence of building material on indoor air pollutants concentration by measurement and prediction. As a met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 62 publications
0
11
0
Order By: Relevance
“…As shown in Table 2, unrated building materials, including adhesives, varnishes, paints, and tiles used in newly constructed or renovated buildings, are major sources of these chemicals. Even in small amounts, these chemicals can have a significant impact on the human body (Arar, Jung and Al Qassimi, 2022). HCHO is released from wood, plywood, and furniture, while VOCs are emitted from textile products found in household appliances (Arar, Jung and Al Qassimi, 2022).…”
Section: Sbs and Who Iaq Standardsmentioning
confidence: 99%
See 2 more Smart Citations
“…As shown in Table 2, unrated building materials, including adhesives, varnishes, paints, and tiles used in newly constructed or renovated buildings, are major sources of these chemicals. Even in small amounts, these chemicals can have a significant impact on the human body (Arar, Jung and Al Qassimi, 2022). HCHO is released from wood, plywood, and furniture, while VOCs are emitted from textile products found in household appliances (Arar, Jung and Al Qassimi, 2022).…”
Section: Sbs and Who Iaq Standardsmentioning
confidence: 99%
“…Even in small amounts, these chemicals can have a significant impact on the human body (Arar, Jung and Al Qassimi, 2022). HCHO is released from wood, plywood, and furniture, while VOCs are emitted from textile products found in household appliances (Arar, Jung and Al Qassimi, 2022).…”
Section: Sbs and Who Iaq Standardsmentioning
confidence: 99%
See 1 more Smart Citation
“…174,175 Exposure to these air pollutants can cause both short-term and long-term cardiorespiratory health problems, including sick building syndrome to the occupants. 176,177 Evidence from the literature shows that exposure to indoor air pollutants can cause chronic obstructive pulmonary disease (COPD), including asthma and lung cancer. 178,179 Although the integration of PCM in buildings is widely known to improve the thermal comfort of occupants, knowledge about its potential to emit indoor air pollutants considering its complex chemical composition levels remains limited in the literature.…”
Section: Cooling Effect Of Pcm Under Extreme Heat Stress In the Outdo...mentioning
confidence: 99%
“…Studies have shown that among the major sources of air pollution are buildings materials, mostly paints, plastic wall materials, wooden materials serving as potential sources of volatile organic compounds (VOCs), HCHO, including airborne microplastics 174,175 . Exposure to these air pollutants can cause both short‐term and long‐term cardiorespiratory health problems, including sick building syndrome to the occupants 176,177 . Evidence from the literature shows that exposure to indoor air pollutants can cause chronic obstructive pulmonary disease (COPD), including asthma and lung cancer 178,179 …”
Section: Potential Impact Of Pcms On Indoor Air Qualitymentioning
confidence: 99%